Handbook of inland aquatic ecosystem management - Jørgensen, Sven Erik, 1934- (Applied ecology and environmental management., 2013)
" ... a book on the subject of lakes and reservoirs is extremely welcome today when fast global changes, including urbanization, global commerce, and climate, are posing-and will pose in the near future-greater stress in our hydrologic systems. The authors present the subject in such a way that the reader will learn not only fundamentals of limnology but also the behavior of lakes and reservoirs both from a physicochemical and an ecosystemic point of view. The book relies on several examples from projects developed by the authors on the ground. This is something that professiona."